2020
DOI: 10.1177/0973703020917502
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Gender Disparity in Nutritional Status and Dietary Intake of Adolescents in Uttarkashi

Abstract: Adolescence is considered to be a nutritionally vulnerable period of life. The current cross-sectional study attempts to assess gender-based differences in nutritional status and dietary intake of a sample of 240 adolescents from Uttarkashi district in the state of Uttarakhand. The data were collected across two schools (Kendriya Vidyalaya, Manera, and Alpine Public School) of Uttarkashi. The nutritional status of each subject was evaluated by using two anthropometric indices, that is, weight-for-age and heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…This can be partly a biological difference and effect of culture and nutrition [ 29 ]. A study in India showed that the dietary intake of energy, iron, calcium and protein was significantly higher in boys than girls [ 30 ]. The slightly higher absence of BCG scar in girls could be explained by less care for girls in Pakistan, where a boy is usually more valued than a girl [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be partly a biological difference and effect of culture and nutrition [ 29 ]. A study in India showed that the dietary intake of energy, iron, calcium and protein was significantly higher in boys than girls [ 30 ]. The slightly higher absence of BCG scar in girls could be explained by less care for girls in Pakistan, where a boy is usually more valued than a girl [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be partly a biological difference and effect of culture and nutrition [32], but could also be partly because of confounding by age, as the girls diagnosed had a higher proportion of adolescents (28%) than the boys (16.9%). A study in India showed that the dietary intake of energy, iron, calcium and protein was signi cantly higher in boys than girls [33]. The slightly higher absence of BCG scar in girls could be explained by less care for girls in Pakistan, where a boy is usually more valued than girl.…”
Section: Discussionmentioning
confidence: 99%
“…This can be partly a biological difference and effect of culture and nutrition [29]. A study in India showed that the dietary intake of energy, iron, calcium and protein was signi cantly higher in boys than girls [30]. The slightly higher absence of BCG scar in girls could be explained by less care for girls in Pakistan, where a boy is usually more valued than a girl [31].…”
Section: Discussionmentioning
confidence: 99%